Metastatic Renal Cell Carcinoma Presenting as Prolonged Pyrexia and Stauffer’s Syndrome: Can a Routine Ultrasound Scan Fail to Detect a Renal Cell Carcinoma? - C. L. Fonseka; A. G. T. A. Kariyawasam; S. A. G. L. Singhapura; C. M. de Silva; T. E. Kanakkahewa; I. G. T. M. Senarathna; C. K. Bodinayake (Case Reports in Radiology)
Background. Prolonged pyrexia and weight loss are recognised paraneoplastic manifestations of renal cell carcinoma (RCC). Stauffer’s syndrome is a rarely described paraneoplastic manifestation, which is described early in the course of RCC. We report a patient who presented with unresolving fever with multiple pulmonary opacities with biochemical evidence of hepatic choleastasis and was later diagnosed to have metastatic RCC with Stauffer’s syndrome. Case Presentation. We report a 54-year-old female who was investigated for a poorly resolving fever and recent weight loss for two months. During her course of illness, she developed bilateral multiple opacifications in the chest radiograph with negative pyogenic, mycobacterial microbiological studies. Despite intravenous antibiotics, her fever continued. She was found to have elevated alkaline phosphatase and gamma-glutamyl transferase and she underwent imaging with ultrasound scan of abdomen twice, which did not reveal demonstrable abnormalities. Later, contrast CT of abdomen and chest was performed and detected a renal cell carcinoma of the right upper pole of the kidney with multiple lung metastases, which was concluded as a metastatic RCC with paraneoplastic Stauffer’s syndrome. Conclusion. Prolonged pyrexia with loss of weight and Stauffer’s syndrome could be features to suggest renal cell carcinoma in the absence of positive microbiological studies. Isoechoic RCC could be missed in routine ultrasonography. When a RCC is suspected in the setting of a pyrexia of unknown origin, ultrasound with doppler or a contrast CT should be requested to aid diagnosis.